The Use of Guided Writing to Improve Students’ Writing Skill - Dieni, Novita Al Ihyak (English Education Department STKIP Al Hikmah Surabaya, 2019)
This article reports a study on the implementation and the improvement of guided writing towards the student’s writing skill and to know the respond of the students towards the implementation of guided writing in the teaching and learning process at the second semester students of English Diploma III of Language and Culture Faculty in 17 Agustus 1945 Semarang University in the academic year of 2017/2018. The second semester students had problems dealing with writing skill. They have difficulties on: (1) expressing their idea in writing; (2) constructing correct sentences; and (3) vocabulary mastery. This study was categorized as a classroom action research. The study was conducted in two cycles. Each cycle was consisted of four steps: plan, action, observation, and reflection. To collect the qualitative data, the researcher used observation. To collect the quantitative data, the researcher conducted tests before and after the research implementation. In this research, the researcher used guided writing and communicative & process approach to improve student’s writing skill. The result of the research shows that guided writing could improve the students’ writing skill. Through guided writing, the students showed great interest to be actively involved to the teaching and learning process. The students were able to construct sentences correctly. In this case, the sentences they constructed were based on the researcher’s explanation. They also used more vocabularies in their writing. Their mean score of the pre-test was 63.3, while their mean score at the post-test, increased up to 76.1.